2007
DOI: 10.1111/j.1743-6109.2006.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Cavernosum Electromyography with Revised Methodology: An Explorative Study in Patients with Erectile Dysfunction and Men with Reported Normal Erectile Function

Abstract: Introduction A lack of standardization of the recording techniques of corpus cavernosum electromyography (CC-EMG) and objective criteria to characterize the recorded signals (CC-potentials) are the main difficulties hindering the clinical application of this method. These difficulties have been recently overcome by revising the recording and interpretation methodology of CC-EMG Aim To assess if CC-EMG performed with the revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The fact that inhibitors of L-type VDCC inhibit spontaneous contractions in isolated strips of corpus cavernosum is consistent with the idea that Ca 2+ influx via this pathway is important for tone generation [1,2,7,8]. However, the ability of human, rabbit and rat corpus cavernosum to develop phasic contractions and phasic electrical activity (such as bursting activity in electromyography studies, spontaneous depolarizations, and spontaneous Ca 2+ -activated Clcurrents) suggests that the intracellular Ca 2+ levels are oscillatory, rather than constant as described by the "window current" mechanism [1,2,[9][10][11][12][13][14][15]. This was confirmed in a recent study where spontaneous Ca 2+ waves were shown to be generated both in individual smooth muscle cells and across intact slices of corpus cavernosum tissue where bursts of Ca 2+ signals could be seen to trigger both phasic and tonic components of contraction [15].…”
Section: Introductionsupporting
confidence: 77%
“…The fact that inhibitors of L-type VDCC inhibit spontaneous contractions in isolated strips of corpus cavernosum is consistent with the idea that Ca 2+ influx via this pathway is important for tone generation [1,2,7,8]. However, the ability of human, rabbit and rat corpus cavernosum to develop phasic contractions and phasic electrical activity (such as bursting activity in electromyography studies, spontaneous depolarizations, and spontaneous Ca 2+ -activated Clcurrents) suggests that the intracellular Ca 2+ levels are oscillatory, rather than constant as described by the "window current" mechanism [1,2,[9][10][11][12][13][14][15]. This was confirmed in a recent study where spontaneous Ca 2+ waves were shown to be generated both in individual smooth muscle cells and across intact slices of corpus cavernosum tissue where bursts of Ca 2+ signals could be seen to trigger both phasic and tonic components of contraction [15].…”
Section: Introductionsupporting
confidence: 77%
“…It has recently been proposed after radical prostatectomy that impairment of penile thermal and vibratory sensory thresholds could reflect cavernous nerve damage. Further studies are mandatory to confirm this finding .…”
Section: Neurophysiological Assessment Of Ed: General Comment and Conmentioning
confidence: 81%
“…The recording of the electric activity of the CC, or the electrocavernosogram (ECG), was introduced in the diagnostic evaluation of erectile dysfunction [8][9][10][11][12][13][14][15]. It provides information on the smooth musculature and autonomic innervation of the penis.…”
Section: Discussionmentioning
confidence: 99%